The Impact of Trade Policy on the Regulation of Export Goods on Indonesia's Economic Growth - Saragih, Elisa Clara; Sinaga, Era Widia Br; Sirait, Melani Manginar; Hutabalian, Relli Anisma; Silaban, Putri Sari Margaret Julianti (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
Trade policy significantly influences the regulation of export goods and economic growth within a country. This study examines the impact of Indonesia's nickel ore export ban policy on its economic growth. The research highlights the role of trade policy in fostering domestic industry development, increasing added value, and addressing trade imbalances. However, the policy has also led to international trade conflicts, particularly with the European Union. Using a qualitative descriptive approach with time-series data, this study finds that the export ban positively affected Indonesia's economic performance, evidenced by an increase in ferro-nickel and iron-steel export volumes and GDP growth trends from 2021 to 2023. Despite its benefits, the policy poses risks such as rising nickel prices and potential market loss. To mitigate these, the government must enhance domestic production, improve the competitiveness of downstream products, and engage in effective economic diplomacy. This research underscores the dynamic interplay between trade policies and global economic challenges, offering valuable insights for policymakers.